Gestalt Psychological Theory on Learning Arabic in The Metaverse Era - Nurul Musyafa’ah; Muhammad Afthon Ulin Nuha (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2022)
This research is intended to: 1) describe the understanding of gestalt theory; 2) understand the experimental results of gestalt theory; 3) know the application of gestalt theory in learning Arabic. The researcher uses a descriptive qualitative approach by suggesting some understanding of gestalt theory from several experts and its application in learning Arabic. The data collection methods used by researchers are observation, questionnaires, interviews, and documentation studies. In analyzing qualitative data, the researcher analyzed books or articles related to gestalt theory, opinions from experts in the world of Arabic language education and theories in learning, and suggestions and criticisms addressed in the research. The results of this study are: 1) Gestalt is a psychological theory that argues that particular objects or events will be viewed as an organized whole; 2) Gestalt theory is determined based on experiments conducted by the figures of this theory on several objects, the results of which show the same conclusion, namely that insight is an essential factor in the development of a person's psychological symptoms; 3) Gestalt theory is quite relevant to be applied in the teaching and learning process of Arabic to help students in developing their scientific insight. The formal finding from this research is that the gestalt theory is one of the psychological theories that base knowledge development on insight. In its application, this theory can also be applied in the learning and teaching process of learning Arabic.